How Does Vocabulary Size Affect Maritime English Achievement? A Correlational Study of Cadets in Sorong Merchant Marine Polytechnic - Sumarta, Ryan Puby; Widarbowo, Dodik; Haryanto, Dwi; Budiarte, Agus (RSF Conference Series: Engineering and Technology, 2023)
English, particularly in the context of maritime communication, has significantly contributed to the education field. Conversely, the efficacy of its educational instruction in Indonesia has been lacking. Several variables influence students' proficiency in acquiring foreign languages; one such factor is their vocabulary size. This research aimed to investigate the relationship between the vocabulary size of cadets and their achievement in maritime English. The research design employed in this study is ex post facto. The researcher employed a vocabulary test and assessed maritime English achievement as the primary instrument in their study. In this instance, the researcher administered a written examination to assess the cadets' vocabulary size. Subsequently, the researcher analyzed the data obtained from the assessment to determine the cadets' performance in maritime English. The findings indicated a statistically significant correlation between the two variables. Hence, the size of one's vocabulary indicates the achievement cadets can attain in their proficiency in maritime English.